“A Two-Edged Sword”: Paternalistic Leadership and Nurses Performance: A Moderated Mediation Model - Safdar, Samyia; Faiz, Shazia; Mubarak, Namra (Frontiers in Psychology, 2021)
Background. The study investigates the impact of paternalistic leadership on the performance of nurses. Furthermore, it looks into the role of self-efficacy as a mediator in the relationship between paternalistic leadership and performance. It also looks into the role of power distance as a moderator. Methods. The study used a quantitative survey-based research approach, with questionnaire responses collected over time. Initially, 315 Chinese nurses were surveyed about their views on paternalistic leadership, self-efficacy, and power distance. While their supervisors were called six weeks later for a dyadic answer, they were asked to offer their thoughts on their performance. AMOS 22 was used for CFA (confirmatory factor analysis) while SPSS 22 was employed for descriptive statistics, such as correlation and regression analysis. Results. The findings demonstrated that paternalistic leadership had a beneficial impact on performance. Furthermore, the role of self-efficacy as a mediator and power distance as a moderating mediator in this relationship has been evidenced. Conclusions. The results suggest that paternalistic leadership has a good impact on nurse performance. Furthermore, self-efficacy as a mediator explains the association between paternalistic leadership and nursing performance adequately. Furthermore, power distance appeared to be a powerful moderator, as the moderated mediation results revealed that in high-power-distance societies, such as China, self-efficacy enhances the link between paternalistic leadership and nursing performance. Limitations and future directions were also discussed.